Common Mutual Fund Ownership and Systemic Risk* - Iselin, Michael; Liao, Scott; Zhang, Haiwen (Helen) (Contemporary Accounting Research, 2021)
ABSTRACT We examine whether bank connections via common mutual fund ownership serve as a contagion channel affecting the systemic risk of the banking system. Examining this relation is important because common mutual fund ownership has increased dramatically over the past 20 years, and a buildup of systemic risk was at the heart of the 2008–2009 financial crisis. We predict and document that the extent of a bank's connection with other banks via common ownership increases its contribution to systemic risk. We further predict and find that this association is primarily driven by passive mutual funds. We provide evidence that common passive ownership results in higher systemic risk through two mechanisms: nondiscretionary sell‐offs of bank stocks and a common pattern of voting. Our results are also robust to two alternate instrumental variable analyses. This study contributes to the literature by documenting an unintended, macro‐level consequence of common mutual fund ownership. Our findings broaden the understanding of common ownership as one mechanism through which systemic risk materializes and should be particularly relevant for regulators who seek to prevent future systemic failures.